Loss and damage from flooding in the Gambela region, Ethiopia - Haile, Alemseged Tamiru; Kusters, K.; Wagesho, N. (Inderscience Publishers, 2013)
In this article, we explore the ways in which people in the Ethiopian Gambela region dealt with the extreme flood that occurred in 2007, with specific attention to the associated loss and damage, i.e., the impacts that people were not able to avoid through preventive and coping measures. We found that all of the 431 surveyed households took preventive measures such as the construction of boundary walls, harvesting premature crops and digging drainage ditches to divert the flood away from croplands. However, these could not prevent widespread negative effects such as damage to houses and crops, the outbreak of diseases, and loss of livestock. To deal with the adverse effects, 50% of the respondents relied on the help of relatives, neighbours or friends for food and money. Such assistance appeared crucial. People were, however, worried about over-using their social networks, especially with floods occurring more regularly. Widening people's agricultural and non-agricultural options, for example through investments in micro-finance services and irrigation systems, will help to increase their coping capacity.